2021
DOI: 10.1002/mp.15239
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐specific effects on sonication heating efficiency during magnetic resonance‐guided focused ultrasound thalamotomy

Abstract: During magnetic resonance-guided focused ultrasound (MRgFUS) thalamotomy for refractory tremor,high temperatures must be achieved and sustained for tissue necrosis. We assessed the impact of both patient-specific as well as procedure-related factors on the efficiency of acoustic energy transfer, or heating efficiency (HE). Methods: Retrospective analysis of 92 consecutive patients (857 sonications) with essential tremor or tremor-dominant Parkinson's disease treated at a single institution. Temperature elevati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…This finding corroborates previous evidence [22]. Finally, several recent studies have addressed technical intraprocedural factors that can influence the efficiency of ultrasound focusing as well as the characteristics of the final lesion [23 & , [24][25][26][27][28]. A detailed description of these studies goes beyond the scope of this clinical review.…”
Section: Movement Disorderssupporting
confidence: 88%
“…This finding corroborates previous evidence [22]. Finally, several recent studies have addressed technical intraprocedural factors that can influence the efficiency of ultrasound focusing as well as the characteristics of the final lesion [23 & , [24][25][26][27][28]. A detailed description of these studies goes beyond the scope of this clinical review.…”
Section: Movement Disorderssupporting
confidence: 88%
“…Lower SDR has been postulated to interfere with transcranial energy transmission via greater attenuation and reflection of ultrasonic energy at the marrow/cortical bone interface ( 9 ). Indeed, clinical studies have shown that SDR affects energy delivery and efficiency ( 9 , 10 ). Based in part on the inclusion criteria of the pivotal trial ( 4 ), the FDA has established an SDR of 0.45 (±0.05) or less as a contraindication for MRgFUS ( 1 ).…”
Section: Introductionmentioning
confidence: 99%